Aggressive Behavior in Children: A Review of the Literature - Fairuzillah, Muhammad Naufal; Listiana, Aan (Elementary Education Study Program School of Postgraduate Studies Universitas Pendidikan Indonesia in collaboration with UPI PRESS, 2020)
This study is a literature review devoted to describing how aggressive behavior occurs in children and certainly how educators’ strategies to handle this issue. Lately, many negative behaviors have been found in children which may stimulate them to be aggressive to others, it has shown some negative indication. Aggressive behavior in children is not only limited to physical actions, but also includes oral actions. While, the main factors that cause children to be aggressive are the role of family environment, school environment, society & cultural environment, and biological factors. This behavior has an adverse effect on the performers and the victims from aggressive acts. Parents and educators are responsible for their children’s behavior and character that can rectify their deviations and encourage good relation with others. It is very important for parents and educators to anticipate their children not to be aggressive because it will affect the children’s character in the future